Towards a range-wide assessment of European eel: recent steps undertaken at the regional scale in the Mediterranean within the GFCM European eel Research Programme, in view of a multiannual Regional management plan - E. Ciccotti; E. Amilhat; M. Bdioui; L. Bendjedid; F. Capoccioni (country:DK, 2023)
Aim of this contribution is to present results of recent initiatives undertaken in the Mediterranean Region to contribute to assessment and management of the European eel (Anguilla anguilla, L. 1758), consistent with the overall strategy carried out for stock recovery and conservation of this species across its entire distribution range.